2014
DOI: 10.1111/bjd.12603
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of early-onset atopic dermatitis in Taiwan: a population-based cohort study

Abstract: Summary Background Atopic dermatitis (AD) often manifests in early childhood and has variable disease course among individual patients. Previous studies regarding the natural course of AD have usually been of small sample size and were not based on nationwide populations. Objectives We aimed to find out the disease duration and remission rate of children with early‐onset AD (onset in the first 2 years of life) in Taiwan, and to determine whether the presence of allergic rhinitis (AR) or asthma affects the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 22 publications
2
29
1
1
Order By: Relevance
“…6,23,28,31,44,45,48 The duration of AD persistence was significantly higher in females (median: 9.0 years; mean ± SE: 12.7 ± 0.2 years) compared with males (median: 7.0 years; mean±SE: 11.7 ± 0.2 years) (HR 1.15; 95% CI 1.04-1.27; P = .006) (Fig 2, E).…”
Section: Ad Persistence By Gendermentioning
confidence: 90%
See 1 more Smart Citation
“…6,23,28,31,44,45,48 The duration of AD persistence was significantly higher in females (median: 9.0 years; mean ± SE: 12.7 ± 0.2 years) compared with males (median: 7.0 years; mean±SE: 11.7 ± 0.2 years) (HR 1.15; 95% CI 1.04-1.27; P = .006) (Fig 2, E).…”
Section: Ad Persistence By Gendermentioning
confidence: 90%
“…After review of the titles and abstracts, 9326 were excluded; an additional 634 articles were excluded after full-text review. In total, 46 studies were included in the review, of which 44 had valid frequency data that could be pooled, 7 had valid data to assess the effects of gender, 6,23,28,31,44,45,48 6 for allergen sensitization, 6,17,23,36,40,45 and 3 for baseline AD severity 17,28,40 on disease persistence. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is presented in Fig 1. …”
Section: Literature Searchmentioning
confidence: 99%
“…Birth cohort studies have suggested that, in up to 70% of cases, AD greatly improves or resolves until late childhood. 107,108 One could speculate that resolving childhood AD may represent an independent endotype of AD. However, several birth cohort studies have shown that severity is one of the strongest risk factor for a non resolving AD.…”
Section: Heterogeneity In Children With Atopic Dermatitismentioning
confidence: 99%
“…However, several birth cohort studies have shown that severity is one of the strongest risk factor for a non resolving AD. 107,108 Therefore, it could also be the case that endotypes do not differ between adults and children with AD, but that children with resolving disease suffer from a milder form of AD, irrespective the endotype they belong to. This theory would be in agreement with our findings in chapter 7, in which we showed that disease severity does not influence cluster membership of adult AD patients.…”
Section: Heterogeneity In Children With Atopic Dermatitismentioning
confidence: 99%
“…An interesting puzzle regarding the nature of AD is that a significant number of children with AD (up to 70%) experience natural remission of their disease before puberty [5]. The natural remission observed in children with AD might be due to a natural induction of immune tolerance.…”
Section: Introductionmentioning
confidence: 99%